HELPING A CHILD IN PRONOUNCING SIMPLE SOUNDS - Каптюх, Татьяна (SWorldJournal, 2021)
The paper considers ways to correct the child's pronunciation of the sound "k". Deficiencies in pronunciation significantly distort the child's speech. The child may have omissions, replacements, shortcomings in the differentiation of sounds. The use of s